Integrating Philosophical Perspectives in Management: A Framework for Improving Organisational Decision Making - Muhamad Tody Arsyianto; Wenny Eka Prasetiawan; Agung Winarno (Manajemen Kreatif Jurnal, 2024)
The incorporation of philosophical viewpoints in management is crucial given the intricacies of organisational decision-making frequently confronted with ethical difficulties. This study seeks to establish a framework that incorporates philosophical principles into managerial practices to enhance decision-making efficacy in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The employed methodology was quantitative analysis utilising Structural Equation Modelling (SEM) to assess the correlation between the implementation of philosophical concepts and decision quality. The findings indicate a substantial disparity in the incorporation of philosophical viewpoints in management and decision-making, with businesses that embrace ethical principles generally yielding judgements that are more sustainable and attuned to stakeholder requirements. The findings underscore the necessity of implementing philosophy-based frameworks in management practices, while also offering direction for organisational leaders to foster a more ethical and innovative workplace culture. This research also creates prospects for more studies on the use of philosophy within a wider corporate setting.